Use of PELC/CpG Adjuvant for Intranasal Immunization with Recombinant Hemagglutinin to Develop H7N9 Mucosal Vaccine - Ting-Hsuan Chen (Vaccines, 2020)
Human infections with H7N9 avian influenza A virus can result in severe diseases with high mortality. Developing an effective vaccine is urgently needed to prevent its pandemic potential. Vaccine delivery routes via mucosal surfaces are known to elicit mucosal immune responses such as secretory IgA antibodies in mucosal fluids, thus providing first-line protection at infection sites. PEG-b-PLACL (PELC) is a squalene-based oil-in-water emulsion adjuvant system that can enhance antigen penetration and uptake in nasal mucosal layers with enhanced mucin interactions. In this study, intranasal immunizations with recombinant H7 (rH7) proteins with a PELC/CpG adjuvant, as compared to the use of poly (I:C) or bacterial flagellin adjuvant, elicited higher titers of H7-specific IgG, IgA, hemagglutination inhibition, and neutralizing antibodies in sera, and increased numbers of H7-specific IgG- and IgA-antibody secreting cells in the spleen. Both PELC/CpG and poly (I:C) adjuvants at a dose as low as 5 μg HA provided an 80% survival rate against live virus challenges, but a lower degree of PELC/CpG-induced Th17 responses was observed. Therefore, the mucosal delivery of rH7 proteins formulated in a PELC/CpG adjuvant can be used for H7N9 mucosal vaccine development.